Effects of Differences in Installation Slope on Growth and Yield of Rice (Oryza sativa L.) Hydroponically - Y.K, Cica; Sukendah, Sukendah; Makhziah, Makhziah (Faculty of Agriculture, Universitas Malikussaleh, 2022)
Rice (Oryza sativa L.) is a staple food for Indonesian people to fulfill their daily needs. Rice planting is expected to be able to produce high value, but nowadays it is constrained by the increasing condition of the land. Hydroponic cultivation is the right solution because it can be done on a narrow area but the response of plants to the slope of the hydroponic land is not yet known. This study aims to determine the effect of the slope of the hydroponic installation on the growth and yield of hydroponic rice plants. The research was carried out from June to September 2022, at the experimental field of the Faculty of Agriculture, UPN